Association between vector-borne pathogen seroprevalence in shelter-housed and owned dog populations in the contiguous United States of America. - Gettings, Jenna R; McMahan, Christopher S; Cleveland, Christopher A; Varela-Stokes, Andrea.; Hubbard, Kris.; Hamer, Sarah A; Walden, Heather S; Yabsley, Michael J (Tufts University. Tisch Library., 2023)
Keywords: Canine, Ticks, Tick-borne diseases, Zoonoses.; Springer Open.